Triboelectric neurostimulator for physiological modulation of leg muscle. (1st December 2022) - Kang, Minseok; Shin, Heejae; Cho, Youngjun; Park, Jaewoo; Nagwade, Pritish; Lee, Sanghoon
Abstract: Neurostimulation using triboelectric nanogenerators (TENGs) has been actively researched. However, only limited neural responses have been demonstrated since the previous TENGs could not change stimululs parameters owing to limited operation design and conditions. To overcome these challenges, we report a rotation-based triboelectric neurostimulator (RoTENS) that allows the continuous modulation of stimulus parameters depending on rotation while generating a constant charge output. The RoTENS adjusts the stimulus parameters by controlling the rotational speed and non-contact method. The electrode materials and patterns were optimized, and the characterization of RoTENS was investigated. Furthermore, the neurophysiological validation of hindlimb modulation in rats was demonstrated. By directly stimulating the sciatic nerve branches using RoTENS, dorsiflexion (max. 13.12°) and plantar flexion (maximum 29.34°), which are major movements of the hindlimb for gait, were induced. Varying the frequency (10–50 Hz) allows the muscle to smoothly shift its physiological state from twitching to fused tetanus. The natural relaxation of the muscle is induced by changing the current amplitude via the height of the rotator (0–6 mm). These results indicate that RoTENS is sufficient to induce the desired physiological response while creating wide-ranging frequencies and amplitudes. We expect that RoTENS will open up new opportunities and possibilities for the use of TENG as neurostimulators. Graphical Abstract: ga1 Highlights: A rotation based triboelectric neuro-stimulator (RoTENS) enables to adjust the stimulus parameters of frequency and current amplitude, respectively, by modulating the rotation speed and non-contact method. RoTENS allows physiological activation of a rat's hindlimb within the frequencies (10-50 Hz), mimicking natural movement of the hindlimb. RoTENS provides a constant charge per pulse during changing stimulus frequency and current amplitude, which opens up new opportunities and possibilities for the use of TENG as novel neurostimulators.